2003
DOI: 10.1038/sj.onc.1206463
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the progression of melanocytic neoplasia using genomic analysis: from fields to cancer

Abstract: Analysis of DNA copy number changes using comparative genomic hybridization in melanocytic neoplasms has revealed distinct patterns of chromosomal aberrations between benign melanocytic nevi and melanoma. Whereas the vast majority of melanoma expresses chromosomal aberrations, blue nevi, congenital nevi, and most Spitz nevi typically show no aberrations. A subset of Spitz nevi shows an isolated gain of chromosome 11p, an aberration pattern not observed in melanoma. These Spitz nevi frequently harbor mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
91
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 29 publications
5
91
0
6
Order By: Relevance
“…It is also possible that the coamplifications are merely a result of genetic instability that increases during tumor progression but do not contribute directly to the phenotypic alterations. 43 The BRAF V600E mutation frequency in our samples was 26%, which is in concordance with other studies 44,45 but the occurrence of this mutation was lower than it has been reported elsewhere. 4,46 We detected two other BRAF mutations that were distinct from the V600E mutation.…”
Section: Discussionsupporting
confidence: 81%
“…It is also possible that the coamplifications are merely a result of genetic instability that increases during tumor progression but do not contribute directly to the phenotypic alterations. 43 The BRAF V600E mutation frequency in our samples was 26%, which is in concordance with other studies 44,45 but the occurrence of this mutation was lower than it has been reported elsewhere. 4,46 We detected two other BRAF mutations that were distinct from the V600E mutation.…”
Section: Discussionsupporting
confidence: 81%
“…[6][7][8][9][10][11][12]17,19 This is reassuring regarding the performance of MelanoSITE. We believe that, in this context, abnormal FISH results clinch the diagnosis, and the lesion can be reported as an outright melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…16 The Abbott Molecular melanoma FISH test was also validated in critical differential diagnoses concerning histologically unequivocal benign and malignant blue nevi, nevoid melanoma, dysplastic nevi, desmoplastic melanoma, lentiginous melanoma, nevi with atypical epithelioid cell component, and Spitz nevi. [6][7][8][9][10][11][12]17,19 Obviously, a FISH test is not needed for histologically unequivocal cases. The only current justification for use of this expensive test in a diagnostic setting is to employ it as a diagnostic adjunct to help classify histologically ambiguous lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations